Concepts of Civilization in Pre-Islamic Poetry: Justifications for Absence and Alternatives for Empowerment - Manshed, Kareem. (Thi Qar Arts Journal, 2024)
Researchers and scholars have often viewed pre-Islamic Arab society as primitive, lacking in civilization, organization, and urbanization. They based this view on various historical and cultural data concerning that society, the most significant of which was its lack of understanding of the concept of the state, placing it in the category of non-historical or static societies. However, a closer examination of the social, political, and intellectual aspects of this society reveals that it was aware of this civilized concept and fully understood its importance. Instead, it replaced it with a set of behavioral variations and internal defense mechanisms, represented by forming alliances and treaties to organize internal affairs. Additionally, it sought to empty any potential political authority of its content by attributing its existence to the realm of gods and ancestors, leaving no room for any living human to be a legislator and holder of comprehensive authority.